2014
DOI: 10.1002/jor.22716
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced changes to the vertebral endplate vasculature affect transport into the intervertebral disc in vivo

Abstract: Intervertebral disc health is mediated in part by nutrient diffusion from the microvasculature in the adjacent subchondral bone. Evidence suggests that a reduction in nutrient diffusion contributes to disc degeneration, but the role of the microvasculature is unclear. The purpose of this study was to induce changes in the endplate microvasculature in vivo via pharmaceutical intervention and then correlate microvasculature characteristics to diffusion and disc health. New Zealand white rabbits were administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…These changes are similar to those found in subchondral bone of OA patients and animal models7. TGFβ released from latent extracellular matrix mobilizes and recruits MSCs232425. MSCs are thought to localize with vasculature26.…”
Section: Discussionsupporting
confidence: 67%
“…These changes are similar to those found in subchondral bone of OA patients and animal models7. TGFβ released from latent extracellular matrix mobilizes and recruits MSCs232425. MSCs are thought to localize with vasculature26.…”
Section: Discussionsupporting
confidence: 67%
“…A recently published study reported angiogenesis in the SB regions of degenerating discs [24]. In another study, researchers induced angiogenesis in the SB of rabbits using nimodipine and investigated changes in contrast enhancement in the NP [25]. Interestingly, their study showed that the relationship between the SB microvasculature and solute transport into the NP was not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a certain amount of cell death following in vivo implantation will be acceptable, so long as the formed matrix is retained and the remaining cell population is sufficient to maintain long‐term homeostasis of the tissue overall. Strategies to enhance nutrient transport into engineered discs in vivo, such as enhancement of the vertebral endplate vasculature or stimulation of convective transport via dynamic loading, may ultimately be necessary for the success of engineered constructs in vivo …”
Section: Challenges For In Vivo Translation Of An Engineered Discmentioning
confidence: 99%
“…12 The permeability, composition, and vascularity of the EP significantly impact diffusion of small molecules into the disc. 13,14 In addition to this challenging nutritional environment, disc cells are also subject to large magnitudes of loading in both compression and torsion during spinal motion associated with normal daily activity. Loads on the intervertebral disc can exceed up to 5 times body weight, depending on nature of the activity.…”
Section: Intervertebral Disc Structure and Mechanical Functionmentioning
confidence: 99%
See 1 more Smart Citation